2007
DOI: 10.1073/pnas.0610983104
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ hematopoietic stem-progenitor cell microRNA expression and function: A circuit diagram of differentiation control

Abstract: MicroRNAs (miRNAs) are a recently identified class of epigenetic elements consisting of small noncoding RNAs that bind to the 3 untranslated region of mRNAs and down-regulate their translation to protein. miRNAs play critical roles in many different cellular processes including metabolism, apoptosis, differentiation, and development. We found 33 miRNAs expressed in CD34؉ hematopoietic stem-progenitor cells (HSPCs) from normal human bone marrow and mobilized human peripheral blood stem cell harvests. We then co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
386
1
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 457 publications
(416 citation statements)
references
References 34 publications
(50 reference statements)
19
386
1
6
Order By: Relevance
“…Most importantly, miR-155 is involved in the process of oncogenesis (40). Under physiologic conditions, this miRNA has been shown to be involved in the differentiation of hematopoietic progenitor cells (17,40). Recent experiments with miR-155-knockdown mice described an important role for miR-155 in the normal function of the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, miR-155 is involved in the process of oncogenesis (40). Under physiologic conditions, this miRNA has been shown to be involved in the differentiation of hematopoietic progenitor cells (17,40). Recent experiments with miR-155-knockdown mice described an important role for miR-155 in the normal function of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, miR-155 was characterized as an oncogenic miRNA and was shown to be dysregulated in a large number of human neoplastic diseases (16). Subsequently, miR-155 was shown to be involved in the modulation of hematopoiesis, and very recently, its importance in the normal function of the immune system has been demonstrated (17)(18)(19).…”
mentioning
confidence: 99%
“…Moreover, miRNAs have been implicated in the control of self-renewal in stem cells (Hatfield and Ruohola-Baker, 2008). Georgantas et al found that miRNA-155 played a role in normal human myelopoiesis, lung differentiation, and erythropoieis, and a recent study has shown that a high level of hsamiR-155 is associated with a poor outcome in lung cancer (Georgantas et al, 2007;Wang et al, 2009b). Thus, the detection of related miRNAs in TICs is an important strategy for the early diagnosis of lung cancer.…”
Section: Monitoring Micrornas Using a Molecularmentioning
confidence: 99%
“…[35][36][37][38] The expression of many miRNAs (e.g., miR-181) fluxuate during hematopoiesis, consistent with recent studies demonstrating a critical role for these transcripts in normal differentiation programs. 35,36,39 Other ncRNAs may serve as a physical linkers between RNA-binding proteins (e.g., translocation in liposarcoma, TLS) and DNA promoter sequences. In this model, the ncRNAs cause an allosteric change within the RNA-binding protein, which, in turn, promotes the association of other transcriptional proteins and represses promoter activity.…”
Section: The Changing Transcriptomementioning
confidence: 99%